Why evangelical Christians are supporting international family planning: A response to Should evangelical Christian organizations support international family planning? - Wiley Henry Mosley (Health for All Nations, 2018)
The article by Monique and Jeffery Wubbenhorst asks the question-Should Evangelical Christian Organizations Support International Family Planning?1 The article's response to this question shows a lack of understanding of the fundamentals of population dynamics in the modern world as well as of the critical role contraceptives play in preventing unintended pregnancies and abortions and promoting maternal and child health. These errors are compounded by selective citation and misrepresentation of the evidence in the scientific literature. This commentary seeks to provide a balanced view of the evidence and correct several unfounded assertions in order to document why evangelical Christians and Christian organizations are, in fact, providing family planning services around the world. Specific points addressed are as follows: fundamentals of the global demographic transition including how the contraceptive revolution has slowed world population growth; the social, economic, and cultural forces driving couples to choose to control their fertility for the welfare of their families; the critical role of contraceptive practice in preventing unintended pregnancies and abortions as well as directly promoting safe motherhood and child health; the evidence that women and couples in less-developed countries desire to control their fertility as attested by the measurement of unmet need for family planning; and the reason why failing to provide poor women and couples in less-developed countries who want to control their fertility with the information and contraceptive methods of their choice is likely to lead to unintended pregnancies and more abortions. Christian health professionals and organizations need to be in the world, working with people of all belief systems, since that is a powerful way for the world to be reached with the love of Jesus and the gospel of salvation.